Exploring the Components of Cosmogenic UHECR, Neutrino, and Diffuse Gamma Ray from High-Energy Astrophysical Objects - Fangsheng Min; Hong Lu; Yiqing Guo (Galaxies)
The development of multimessenger astrophysics allows us to probe various background particles from the distant early universe. Up to now, much effort has been made researching the emission and radiation of diverse steady or transient astrophysical sources. We review the potential accelerating, escaping, propagating, and radiation process of high-energy particles under specific circumstances for regular astrophysical sources and briefly discuss the underlying contribution from their emissions to the intensity of ultrahigh-energy cosmic ray, TeV-PeV cosmic neutrino, and the diffuse gamma-ray background, aiming to find a possible common origin.